Feasibility Study of Canned Smoked Fish as the Micro Enterprises in South Sumatra Province, Indonesia - Hasmawaty; Christofora Desi Kusmindari; Muhammad Faizal (Jurnal Optimasi Sistem Industri, 2022)
This paper analyzes several aspects (technical, marketing, economic, social, and financial) of canned smoked fish (Pangasius) as a micro-industry in South Sumatra Province, Indonesia. This article adopts mix-methods. A quantitative method is used to explain technical, marketing, economic, and financial aspects, while the social aspect is explained using a qualitative method. The author collects the Pangasius species sample from nine districts in South Sumatra Province for the technical aspect. This sample transformed into canned smoked fish using several steps: preparation, making and cooking, filling process, exhausting, sealing sterilization, and cooling process. The author also collects secondary data and interviews several key informants to analyze the non-technical aspect of the canned smoked fish industry. A canned smoked fish (Pangasius) has excellent potential to develop as a micro-enterprise in South Sumatra, Indonesia. In the long-term, it could be an instrument for the local government to increase citizens' well-being based on local resources and penetrate the ASEAN free trade area. In a short time, it could be an instrument for the local government to manage the economic effect of COVID-19 in South Sumatera, Indonesia. This study could be a baseline for the government to create a policy for developing the smoked fish industry. The result of this study could be a second opinion in planning capital investment within the smoked fish industry at the SSP for the investor and the entrepreneur.